Critical Management Studies: From One‐Dimensional Critique to Three‐Dimensional Scepticism - Alvesson, Mats; Spicer, André (Journal of Management Studies, 2026)
Abstract Critical Management Studies (CMS) has largely relied on one‐dimensional critique which focus on the negation of a dominant social order. This strong focus has made the field increasingly stale and preoccupied with standard objects for critique. This paper suggests that if CMS is to move beyond these problems, it needs to develop three‐dimensional thinking, including understanding, questioning, and reparation. Drawing on the idea of ‘reparative critique’ (Sedgwick, 1997), we outline what this looks like in practice and how it might be done by practitioners of CMS. We argue that reparative critique involves three steps of understanding, developed through empirical inquiry relaxing assumptions and thick description, critique developed through exploring dilemmas and examining ironies, and reparation which is created through deflation and concept creation. By working through these three steps, we think it is possible for CMS to move beyond identifying the ‘dark side’ and begin to identify positive visions for the future of management.